New construction of strongly relatively nonexpansive sequences by firmly nonexpansive-like mappings - Işık, Hüseyin; Haddadi, Mohammad Reza; Parvaneh, Vahid; Park, Choonkil; Kornokar, Somayeh (Mdpi, 2020)
In recent works, many authors generated strongly relatively nonexpansive sequences of mappings by the sequences of firmly nonexpansive-like mappings. In this paper, we introduce a new method for construction of strongly relatively nonexpansive sequences from firmly nonexpansive-like mappings.
Parvaneh, Vahid/0000-0002-3820-3351; Isik, Huseyin/0000-0001-7558-4088; Park, Choonkil/0000-0001-6329-8228
Keywords: Banach space; Firmly nonexpansive-like mapping; Fixed point; Mapping of type (r); Mapping of type (sr)